Challenges to Interaction between EAEU and EU - Natalia Genrikhovna Zaslavskaya (Управленческое консультирование)
This article is devoted to the current challenges to interaction between the EAEU and EU. It is a highly crucial issue for academic research due to significant role of regional integration project in the contemporary international system and growing cooperation between various regions. In the article, major problems undermining cooperation between the Eurasian and the European integration project were examined. These problems included such issues as political, institutional, geopolitical, conceptual contradictions and values differences. As a result of this research, it was demonstrated that political interests and reasoning prevail over economic interests and reasoning. The practical importance of this article is determined by evaluation of major issues preventing cooperation between the two integration alliances.